Rare earth elements in fertilizers and their chemical behavior in soils of contrasting mineralogy and texture - Dinali, Guilherme Soares (2017)
Rare earth elements (REY) are a group of 17 elements of an ever-growing presence in present-day industries, agriculture, and in everyday life. Phosphate ores are well-known for containing REY in a wide range of contents. Such phosphates are raw materials of many fertilizers that have been constantly applied to soils, especially in Tropical agroecosystems. Because of that, the environmental concentrations of REY are expected to increase accordingly. Our current understanding of the role of different P products as carriers of REY to soils is still incipient, especially regarding the extent to which the original REY content in raw materials remains in their respective products and the changes in crystalline phases associated with the phosphate ore processing. Furthermore, while soils have been considered important sinks for such elements through addition of fertilizers and other sources of REY, yet little research has been conducted concerning REY contents, inputs, and behavior in such ecosystems. Thus, to better understand REY contents in P fertilizers - a major diffuse source of REY to environment -, as well as REY sorption on soils of different genesis - a major sink of REY -, the present study aimed to: i) evaluate REY in phosphate concentrates used as raw materials in major phosphate industries in South America as well as in final products – including P fertilizers, di-calcium phosphate, and phosphogypsum –, in order to characterize their REY contents, signatures, and REY-carrying crystalline phases; and ii) evaluate the adsorption behavior of all REY in soils under different experimental conditions in order to model and predict sorption and fate of REY in soils. Regarding phosphate products, our results showed that the REY content in raw materials and products from the phosphate industry in South America is highly variable. Considering materials of igneous origin, the phosphate concentrate from the Catalão Minerochemical Complex presented the highest total REY content (∑REY up to 16,650 mg kg-1) and the highest concentrations of light REY(∑LREY/∑REY ~98%). A great variety of mineral phases were found not only in phosphate concentrates but also in final products, with the apatite-group appearing as the main REYcarrying crystalline phase. The REY contents and composition in the final products were generally strongly influenced by their respective raw materials, resulting in a strong match of REY signatures, which reinforces the usefulness of REY signatures as accurate tools for tracing the origin and provenance of final products of the P fertilizer industry. With respect to sorption experiments, the different REY were sorbed in similar amounts at the natural soils pH's. REY sorption increased with increasing pH, especially in a tropical soil. Cerium is the REY sorbed in higher amounts whereas lutetium is the lowest sorbed REY, irrespectively of the studied soil. The Langmuir model was efficiently used to fit adsorption data and to estimate maximum adsorption capacity (REYMAC) and sorption strength (KL), except for sandy tropical soils. The REY buffering capacity (REYMBC) has demonstrated to be a great parameter to understand REY behavior on soils. Considering the ever-increasing importance of REY as emerging contaminants, our findings are relevant to predict REY behavior in agroecosystems, as well as REY fate and transport in soils of contrasting mineralogy.